Human Rights in the Contemporary World - Corrigan, Trudy (IntechOpen, 2022)
This book is a collection of narratives and research that explores our understanding of human rights in the contemporary world. The chapters highlight the narrative and experiences of researchers and academics who seek to ensure that human rights are implemented in policies and practices in their communities, their countries, and the global world. The book presents contemporary themes of the United Nations Human Rights in terms of current policies and practices, legislative reform, property rights, liberty, security, and freedom of expression. It also provides a comprehensive understanding of the importance of human rights across a number of fields of study that are very relevant in our contemporary world today.